Pengembangan bahan ajar fisika materi fluida terintegrasi literasi baru dan bencana untuk meningkatkan hasil belajar siswa kelas XI - Nurul Azkia Firmonia; Asrizal A; Fatni Mufit (PILLAR OF PHYSICS EDUCATION, 2020)
The 4.0 Industrial Revolution era that is currently being faced is based on digitalization, so that new literacy and disasters are needed in facing this era. The 2013 curriculum is one of the government’s efforts to accept this 4.0 revolution. The purpose of the 2013 curriculum is to increase student competence. Based on preliminary research that integration of literacy in learning were still low. Solution of this problem is to develop physics learning material that contain new literacy and disasters. The method that used in this research was Research and Development (R&D). The object of research was physics learning material on fluid material to increase new literacy and disaster. The data collection instruments used were preliminary research, validity dan practicality test questionnaire. The data analysis technique used was descriptive statistical analysis. The preliminary research instrument based on observation, book analysis, and analysis test literacy student. The average of value observation that integration literacy in learning  was still low with value 34.72, the result of analysis in five physics book was still enough with average value 41.47, the result of literacy test was still low with average value 40.00. The validity instrument of physics learning material on fluid material to increase new literacy and disaster consists of four components, namely the feasibility of content, presentation, linguistics, and graphic. Validity of physics learning material on fluid material to increase new literacy and disaster was very good with average value 86.27. The practicality instrument consists of four components, namely the easy to use, interesting, clarity, and benefits. Practicality of physics learning material on fluid material to increase new literacy and disaster according to teacher was very good with average value 83,65 and according to student was good with average value 79.52. Physics learning material on fluid material to increase new literacy and disaster for class XI is valid and practical.